Utilisation of malaria preventive measures during pregnancy and birth outcomes in Ibadan, Nigeria - Tongo Olukemi O; Orimadegun Adebola E; Akinyinka Olusegun O (BMC, 2011)
Abstract Background Malaria remains a major public health problem in sub Saharan Africa and the extent of utilisation of malaria preventive measures may impact on the burden of malaria in pregnancy. This study sought to determine the association between malaria preventive measures utilized during pregnancy and the birth outcomes of birth weight and preterm delivery. Methods This cross sectional survey involved 800 mothers who delivered at the University College Hospital, and Adeoyo Maternity Hospital, Ibadan. Data obtained included obstetric information, gestational age, birth weight and self reported use of malaria prevention strategies in index pregnancy. Results Most (95.6%) mothers used one or more malaria control measures. The most commonly used vector control measures were window net (84.0%), insecticide spray (71.5%) and insecticide treated bed nets (20.1%), while chemoprophylactic agents were pyrimethamine (23.5%), Intermittent Preventive Treatments with Sulphadoxine-Pyrimethamine (IPTsp) (18.5%) and intermittent chloroquine (9.5%) and 21.7% used herbal medications. The mean ± SD birthweight and gestational age of the babies were 3.02 kg ± 0.56 and 37.9 weeks ± 2.5 respectively. Preterm delivery rate was 19.4% and 9% had low birth weight. Comparing babies whose mothers had IPTsp with those who did not, mean birth weight was 3.13 kg ± 0.52 versus 3.0 kg ± 0.56 (p = 0.016) and mean gestational age was 38.5 weeks ± 2.1 versus 37.8 weeks ± 2.5 (p = 0.002). The non-use of IPTsp was associated with increased risk of having low birth weight babies (AOR: 2.27, 95% CI: 0.98; 5.28) and preterm birth (AOR: 1.93, 95% CI: 1.08, 3.44). The non use of herbal preparations (AOR: 0.55, 95% CI: 0.36, 0.85) was associated with reduced risk of preterm birth. The mean ± SD birth weight and gestational ages of babies born to mothers who slept under ITNs were not significantly different from those who did not (p = 0.07 and 0.09 respectively). Conclusions There is a need for improved utilisation of IPTsp as well as discouraging the use of herbal medications in pregnancy in order to reduce pregnancy outcome measures of low birth weight and preterm deliveries in this environment.